Characterization of the logistic process of products with plastic containers in dairy companies in the department of Norte de Santander - Eng. Adriana Bautista Villamizar1, Mg. Leonor JaimesCerveleón, Wilberto Cabrales Castrillo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The dairy sector in the department of Norte de Santander is considered a booming sector in the economy of the region. Due to the fact that these companies have a variety of product lines, it is considered important to characterize the logistic process, as well as the quantity and types of plastic packaging used by the company, being its management a competitive advantage in the market: This article presents the characterization of the logistic process currently carried by the dairy producing companies in the department, taking into account variables such as production, procurement, storage, purchases, inventories, distribution and customer service, related to all these products that use for their packaging or packaging plastic containers, forming a fundamental part of the operational and strategic processes of a company, and additionally expectations of implementing a reverse logistics within the processes were taken into account. Finally, it is presented as a result the current diagnosis of all these variables of the logistics process in terms of plastic containers by the dairy companies in the department, considering that this type of companies need to improve aspects concerning the logistics system, which allows them to have greater control and competitiveness in the market, and finally they can contribute within their process to the sustainability of the company.